Math, asked by kramsai32, 6 months ago

(-1/2)^-3/-(1/2)-4 - (-1/2)^-5/-(1/2)^-6​

Answers

Answered by dushyanth3301
5

ANSWER

(i) To verify : A×(B∩C)=(A×B)∩(A×C)

We have B∩C={1,2,3,4}∩{5,6}=ϕ

∴ L.H.S = A×(B∩C)=A×ϕ=ϕ

A×B={(1,1),(1,2),(1,3),(1,4),(2,1),(2,2),(2,3),(2,4)}

A×C={(1,5),(1,6),(2,5),(2,6)}

∴R.H.S.=(A×B)∩(A×C)=ϕ

∴L.H.S=R.H.S

Hence A×(B∩C)=(A×B)∩(A×C)

(ii) To verify: A×C is a subset of B×D

A×C={(1,5),(1,6),(2,5),(2,6)}

B×D={(1,5),(1,6),(1,7),(1,8),(2,5),(2,6),(2,7),(2,8),(3,5),(3,6),(3,7),

(3,8),(4,5),(4,6),(4,7),(4,8)}

We can observe that all the elements of set A×C are the elements of set B×D

Therefore A×C is a subset of B×D

hope it is helpful

make me as brineliest

Answered by chinmxyi
9

Answer:

hhgggffvbhxjdgjsjtefjdfjsgjegjdgjdcndvkd

Similar questions